1968
DOI: 10.1172/jci105744
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and biological properties of iodoinsulin labeled with one or less atoms of iodine per molecule

Abstract: AB S T RAC T Experiments were designed to compare the distribution of free and antibody-bound unlabeled insulin to the distribution of free and antibody-bound insulin-125I. The insulin antibody was incorporated in a specific immune precipitate similar to the one used by Hales and Randle for the radioimmune assay of insulin. Insulin which was not bound by the specific immune precipitate was measured by the immune hemolysis inhibition assay. This report contains evidence that the addition of the unlabeled insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

1969
1969
1994
1994

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…Paper chromatography, however, to a remarkable degree identifies insulin, which has preserved its immunological integrity; the same conclusions may be drawn from our in vitro experiments. Studies on animals by Izzo and coworkers, 10 and later by Arquilla and coworkers, 11 suggest also that the biological activity as well as the rate of breakdown of insulin is diminished after iodination. In this connection it is relevant to note that Yalow and Berson 12 a decade ago demonstrated that the protein-precipitable radioactivity showed a four-fold variation with different lots of I-131 insulin when measured one hour after administration.…”
Section: Discussionmentioning
confidence: 93%
“…Paper chromatography, however, to a remarkable degree identifies insulin, which has preserved its immunological integrity; the same conclusions may be drawn from our in vitro experiments. Studies on animals by Izzo and coworkers, 10 and later by Arquilla and coworkers, 11 suggest also that the biological activity as well as the rate of breakdown of insulin is diminished after iodination. In this connection it is relevant to note that Yalow and Berson 12 a decade ago demonstrated that the protein-precipitable radioactivity showed a four-fold variation with different lots of I-131 insulin when measured one hour after administration.…”
Section: Discussionmentioning
confidence: 93%
“…The validity of iodoinsulin as a tracer for native insulin has been repeatedly questioned (31,32). Lower values for MCR have been reported by those investigators (1, 33, 34) who used tracer radioinsulin in comparison with the findings of those (1,5,35) who employed cold insulin (Table VI).…”
Section: Discussionmentioning
confidence: 99%
“…It is established, in fact, that the rate and extent of degradation of iodoinsulins are inversely related to the iodination degree (36,37). Lightly iodinated insulin, on the other hand, retains full immunological reactivity (32,38), biological activity (32,14), and binding to membrane receptors (13) and is efficiently degraded by fat (39) and liver (37,40) cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since chemical determination of insulin in high specific activity preparations at low insulin concentrations is difficult, the quantification of insulin for the purposes of calculating the specific activities attained in the various [ 3 H]insulin preparations used in this investigation, was done by standard radio immuno- Table 1. Distribution of radioactivity in a commercial L- [2,3,4,5, Hlphenylalanine preparation. The L- [2,3,4,5, HJphenylalanine was run with 1 Mg carrier on a Cellulose MN-30 TLC plate developed with n-butanol/acetic acid/ water (12:3:5) and quantitatively analysed by scraping the stationary phase off the plate and counting in liquid scintillation fluid.…”
Section: Resultsmentioning
confidence: 99%
“…Distribution of radioactivity in a commercial L- [2,3,4,5, Hlphenylalanine preparation. The L- [2,3,4,5, HJphenylalanine was run with 1 Mg carrier on a Cellulose MN-30 TLC plate developed with n-butanol/acetic acid/ water (12:3:5) and quantitatively analysed by scraping the stationary phase off the plate and counting in liquid scintillation fluid. The insulin had been separated from the coupling mixture by exclusion chromatography (see Fig.…”
Section: Resultsmentioning
confidence: 99%